2021
DOI: 10.3389/fonc.2021.711402
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Biomarkers and Immunotherapeutic Targets Among CXC Chemokines in Pancreatic Adenocarcinoma

Abstract: BackgroundPancreatic cancer is one of the principal causes of tumor-related death worldwide. CXC chemokines, a subfamily of functional chemotactic peptides, affect the initiation of tumor cells and clinical outcomes in several human malignant tumors. However, the specific biological functions and clinical significance of CXC chemokines in pancreatic cancer have not been clarified.MethodsBioinformatics analysis tools and databases, including ONCOMINE, GEPIA2, the Human Protein Atlas, DAVID, GeneMANIA, cBioPorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Chemokines regulate cancer‐related inflammation, tumor microenvironment, tumor growth, and metastasis 39 . Recently, chemokine‐based risk signatures have showed a good prediction for clinical outcome and immunotherapy response in lung adenocarcinoma and pancreatic adenocarcinoma 40,41 . Additionally, a dysregulated chemokine network is one of the characteristics of glioma 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokines regulate cancer‐related inflammation, tumor microenvironment, tumor growth, and metastasis 39 . Recently, chemokine‐based risk signatures have showed a good prediction for clinical outcome and immunotherapy response in lung adenocarcinoma and pancreatic adenocarcinoma 40,41 . Additionally, a dysregulated chemokine network is one of the characteristics of glioma 39 .…”
Section: Discussionmentioning
confidence: 99%
“… 39 Recently, chemokine‐based risk signatures have showed a good prediction for clinical outcome and immunotherapy response in lung adenocarcinoma and pancreatic adenocarcinoma. 40 , 41 Additionally, a dysregulated chemokine network is one of the characteristics of glioma. 39 Thus, we performed the comprehensive analysis of the chemokine genes in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Many of chemokines are important for the regulation of chemotaxis of immune cells, especially T lymphocyte, monocytes/macrophages, and eosinophils. 34 As listed in Table 2 , SLC7A11 expression was significantly positively correlated with T lymphocyte-related chemokines and monocyte/macrophage-related chemokines (CCL22), mast cell-related chemokines (CCR3 and CXCR4), eosinophil-related chemokines (CCL24) in UCEC. These findings indicate that SLC7A11 expression may regulate immune cell infiltration in UCEC.…”
Section: Resultsmentioning
confidence: 89%
“…Recently, it has been shown that chemokine-based risk signatures show good predictive power in clinical prognosis and response to immunotherapy in glioma, lung adenocarcinoma and pancreatic adenocarcinoma. ( Chen et al, 2021 ; Huang et al, 2021 ; Fan et al, 2022 ). As a result, we investigated thoroughly the chemokine genes in ccRCC.…”
Section: Discussionmentioning
confidence: 99%